2009
DOI: 10.1186/1471-2431-9-6
|View full text |Cite
|
Sign up to set email alerts
|

Psychological adjustment and quality of life in children and adolescents following open-heart surgery for congenital heart disease: a systematic review

Abstract: Background: Children with congenital heart defects (CHD) requiring open-heart surgery are a group at high risk for health-related sequelae. Little consensus exists regarding their long-term psychological adjustment (PA) and health-related quality of life (QoL). Thus, we conducted a systematic review to determine the current knowledge on long-term outcome in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
164
2
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(195 citation statements)
references
References 54 publications
8
164
2
10
Order By: Relevance
“…Penelitian di Norwegia, pada anak usia 7-12 tahun, ditunjukkan bahwa anak dengan PJB yang telah menjalani operasi Cardiopulmonary bypass (CPB) mengalami masalah kualitas hidup. 8 Gangguan fungsi kognitif pada lesi sianosis tidak hanya akibat dari hipoksia kronis, tetapi akibat faktor lain yang memengaruhi, seperti kekhawatiran orang tua yang berlebihan sehingga mereka terlalu menjaga anaknya. 9 Pada orang tua, stres berhubungan dengan harapan agar anaknya bisa hidup normal seperti anak lainnya.…”
Section: Pembahasanunclassified
“…Penelitian di Norwegia, pada anak usia 7-12 tahun, ditunjukkan bahwa anak dengan PJB yang telah menjalani operasi Cardiopulmonary bypass (CPB) mengalami masalah kualitas hidup. 8 Gangguan fungsi kognitif pada lesi sianosis tidak hanya akibat dari hipoksia kronis, tetapi akibat faktor lain yang memengaruhi, seperti kekhawatiran orang tua yang berlebihan sehingga mereka terlalu menjaga anaknya. 9 Pada orang tua, stres berhubungan dengan harapan agar anaknya bisa hidup normal seperti anak lainnya.…”
Section: Pembahasanunclassified
“…Some studies have reported that poorer QOL is related to cardiac instability [15], greater disease severity [8,12], and poorer motor functioning and autonomy [11], although no differences were found for the variables of gender, age, and marital status [15]. Some studies have found poorer psychological wellbeing and QOL in CHD patients than in healthy control subjects [18,19], whereas others have claimed there is no difference between the two groups.…”
mentioning
confidence: 99%
“…[1][2][3][4] QoL is a multidimensional concept, inherently subjective, in which the self-report element for all individuals, including children, is important. 5,6 Although it is well recognized in industrialized countries that ascertaining children' s views of their QoL is essential for improving health care strategies, assessment of subjective well-being in children is still not common in the United States and the United Kingdom.…”
mentioning
confidence: 99%